Configuration effect and mechanical behavior of particle reinforced aluminum matrix composites. (February 2023) - Lin, Zichang; Su, Yishi; Qiu, Caihao; Yang, Jingyu; Chai, Xushun; Liu, Xuyang; Ouyang, Qiubao; Zhang, Di
Abstract: Strength-toughness matching of particle reinforced metal matrix composites (PRMMCs) has become a key issue to meet their increasing requirements for aerospace, defense and transportation. Composite configuration (i.e., spatial distribution of reinforced particles) can make effects on the mechanical properties of PRMMCs. In this work, structural modeling and properties simulations of silicon carbide particle reinforced aluminum matrix composites were combined with particle swarm optimization to screen the composite configurations with superior mechanical performances. Configuration effect on the strength-toughness matching of PRMMCs were quantitatively indicated by analyzing the particle clustering degree and particle size gradation in the screened composite configurations. A particle clustering parameter was proposed to quantify the particle clustering effect, in which the composite configurations with serious particle clusters yielded much lower toughness. Composite configurations with increasing small particles can produce larger strength and toughness, while the particle size gradation can be presented by the linear and sigmoid functions respectively. Graphical abstract: